MULTISTAGE SEDIMENTARY AND METAMORPHIC ORIGIN OF PYRITE AND GOLD IN THE GIANT SUKHOI LOG DEPOSIT, LENA GOLD PROVINCE, RUSSIA - Large R.R.; Maslennikov V.V.; Robert F.; Danyushevsky L.V.; Chang Z. (My University, 2007)
Gold mineralization at Sukhoi Log in eastern Siberia is hosted in a deformed Neoproterozoic organic-bearing and pyritic black shale and siltstone sequence that is folded into a tight overturned anticline. The deposit contains about 30 million ounces of gold at an average grade of 2.0 g/t Au and is one of the largest known undeveloped gold resources. The high-grade gold zone forms a gently dipping tabular body in the core of the anticline. The best gold grades occur in narrow, bedding-parallel pyrite-quartz veinlets that have been folded during the main deformation event. Lower grade gold is associated with disseminated pyrite developed in and around the high-grade core of the deposit. Detailed paragenetic studies of the mineralization and host rocks have defined six stages of pyrite development in the carbonaceous sediments. The two earliest forms of pyrite, termed py1 and py2, are commonly developed in stratiform layers of micron-sized crystals, framboids and fine euhedra, which are interpreted as synsedimentary to early diagenetic in origin. Coarser grained, bedding-parallel aggregates of inclusion-rich pyrite, termed py3, contain inclusions of arsenopyrite, native gold and gold tellurides and are interpreted to form during late diagenesis and earliest deformation. Coarse euhedral pyrite, py4, overgrows the earlier pyrite (py1, py2, and py3), and the slaty cleavage developed in the host rocks, indicating a syndeformation timing. Late-stage, inclusion-free pyrite, py5, overgrows and replaces earlier sulfides and is considered to be syn- to late deformation. Laser-ablation inductively coupled plasma mass spectrometry (LA-ICPMS) analyses of the various pyrite types indicate that the synsedimentary py1 contains the highest levels of invisible gold, varying from 0.4 to 12.1 ppm, with a mean of 3.22 ppm Au, and 1,900 ppm As. Py1 is also enriched in a suite of trace elements (Mo, Sb, Ni, Co, Se, Te, Ag, Cu, Pb, Zn, Mn, Ba, Cr, U, V), which are similar to those concentrated by organic processes in euxinic sedimentary environments. Later generations of pyrite, from py2 to py5, including pyrite in bedding-parallel pyrite-quartz veinlets, contain progressively lower contents of invisible gold and most other trace elements. However, this metamorphic and postmetamorphic pyrite contains microinclusions of free gold, arsenopyrite, pyrrhotite, sphalerite, and chalcopyrite. The paragenetic, textural, and chemical relationships at Sukhoi Log suggest that gold was clearly initially introduced prior to cleavage development, accompanying sedimentation of the organic-rich shales and fixed during diagenesis within the structure of diagenetic arsenian pyrite. Subsequently, accompanying deformation, gold was liberated from recrystallized diagenetic pyrite to become concentrated as free gold and gold tellurides within metamorphic pyrite and folded bedding-parallel pyrite-quartz veinlets. Two key processes are considered vital to the formation of the Sukhoi Log deposit: original synsedimentary and early diagenetic concentration of gold, dissolved within arsenian pyrite in organic-rich black shales, and metamorphic processes that liberated gold from the early forms of arsenian pyrite, to be concentrated as free gold, and gold tellurides within late diagenetic and metamorphic pyrite and associated pyrite-quartz veinlets in the core of an overturned anticline. These ore-forming processes are unlikely to be unique to Sukhoi Log; other black-shale and turbidite-hosted deposits that occur in rifted continental margin environments, which have undergone collision and basin inversion, may form by similar processes. © 2007 Society of Economic Geologists, Inc.
Keywords: Sukhoi Log; gold; pyrite